2018
DOI: 10.1016/j.ijrobp.2018.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Spot Size and Spacing on the Quality of Robustly Optimized Intensity Modulated Proton Therapy Plans for Lung Cancer

Abstract: Robust optimization with a small spot-machine significantly improves heart and esophagus sparing, with comparable plan robustness and interplay effects compared with robust optimization with a large-spot machine. A small-spot machine uses a larger number of spots to cover the same tumors compared with a large-spot machine, which gives the planning system more freedom to compensate for the higher sensitivity to uncertainties and interplay effects for lung cancer treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
93
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 57 publications
(97 citation statements)
references
References 60 publications
4
93
0
Order By: Relevance
“…Larger number of spots will be needed to cover the same target volume if small‐spot proton machine was applied, which was also reported in a recent study . In the same study it was stated that interplay effects should be considered before IMPT treatment plan was delivered to lung cancer patients …”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…Larger number of spots will be needed to cover the same target volume if small‐spot proton machine was applied, which was also reported in a recent study . In the same study it was stated that interplay effects should be considered before IMPT treatment plan was delivered to lung cancer patients …”
Section: Introductionmentioning
confidence: 53%
“…However, a simulation study showed that small‐spot IMPT ( σ : 2~4 mm) could be less robust toward motion and interplay effects than large‐spot IMPT ( σ : 8~17 mm) . Larger number of spots will be needed to cover the same target volume if small‐spot proton machine was applied, which was also reported in a recent study . In the same study it was stated that interplay effects should be considered before IMPT treatment plan was delivered to lung cancer patients …”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Breath hold and abdominal compression would just as audio‐visual biofeedback limit the motion uncertainties. Complementary ways to increase plan quality under motion is to make educated choices of planning parameters, such as beam angles and spot size …”
Section: Discussionmentioning
confidence: 99%
“…Complementary ways to increase plan quality under motion is to make educated choices of planning parameters, such as beam angles 44 and spot size. 49,50 Averaging effects over fractions are not taken into account in the interplay evaluation. For moderate motion and normally fractionated treatments, these effects could mitigate the interplay effects to a fairly large extent.…”
Section: Discussionmentioning
confidence: 99%